2022
DOI: 10.1021/acs.jproteome.2c00601
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Multiomics of Lipids, N-Glycans, and Tryptic Peptides on a Single FFPE Tissue Section

Abstract: Mass spectrometry imaging (MSI) is an emerging technology that is capable of mapping various biomolecules within their native spatial context, and performing spatial multiomics on formalin-fixed paraffin-embedded (FFPE) tissues may further increase the molecular characterization of pathological states. Here we present a novel workflow which enables the sequential MSI of lipids, N-glycans, and tryptic peptides on a single FFPE tissue section and highlight the enhanced molecular characterization that is offered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Moreover, trends towards the integration of spatial proteomics data with those obtained from complementary molecular levels, such as the lipidome and N-glycome, have also been reported and serve to strengthen the discriminatory power obtained by spatial proteomics. In particular, Denti et al [26] have recently reported the possibility to perform spatial multi-omics of these three molecular classes on a single FFPE tissue section, which can be particularly relevant in instances where clinical tissue may be scarce, such as for low incident diseases or those which require multiple histological and immunohistochemical assessments [27]. This approach represents a further promising avenue considering that it has already been highlighted that using classifiers which span multiple omics levels can improve the correlation of molecular features with clinical endpoints and improve patient stratification [28].…”
Section: Methodological Advancementsmentioning
confidence: 99%
“…Moreover, trends towards the integration of spatial proteomics data with those obtained from complementary molecular levels, such as the lipidome and N-glycome, have also been reported and serve to strengthen the discriminatory power obtained by spatial proteomics. In particular, Denti et al [26] have recently reported the possibility to perform spatial multi-omics of these three molecular classes on a single FFPE tissue section, which can be particularly relevant in instances where clinical tissue may be scarce, such as for low incident diseases or those which require multiple histological and immunohistochemical assessments [27]. This approach represents a further promising avenue considering that it has already been highlighted that using classifiers which span multiple omics levels can improve the correlation of molecular features with clinical endpoints and improve patient stratification [28].…”
Section: Methodological Advancementsmentioning
confidence: 99%
“…The new MSI data computation method can be promptly translated into real practice when implemented in environments, such as RStudio, Python, MATLAB, and Delphi. Multivariate analytic methods, machine learning, and deep learning models are introduced into the MSI data processing tasks, such as automatic spatial segmentation [38,39], discriminative ion picking and latent feature extraction [40][41][42], region-specific matrix effect normalization [43], 3D image construction [44,45], high-quality image recovery by over-or sparse-sampling [46,47], co-localization (co-registration) among multi-modal images [48,49], and spatial multi-omics imaging data integration [50,51].…”
Section: Msi Data Analysismentioning
confidence: 99%
“…Many successful cases using heat treatment were shown in the spatial characterization of protein assisted by various recent techniques including a nanodroplet in a pot system. 29,30 Heating the fixed sample in acidic or basic buffer partially removes the crosslinks and often facilitates subsequent trypsinization needed for MS-based proteomics/ peptidomics investigation of tryptic fragments. 31−35 However, these traditional approaches have not been effective in dealing with the single-cell analysis of FF tissue.…”
mentioning
confidence: 99%
“…HIAR has been widely used in immunohistochemistry to improve the ability to detect antigens via restoring access to binding sites and their proper spatial confirmations. Many successful cases using heat treatment were shown in the spatial characterization of protein assisted by various recent techniques including a nanodroplet in a pot system. , Heating the fixed sample in acidic or basic buffer partially removes the crosslinks and often facilitates subsequent trypsinization needed for MS-based proteomics/peptidomics investigation of tryptic fragments. …”
mentioning
confidence: 99%